2002
DOI: 10.1055/s-2002-23574
|View full text |Cite
|
Sign up to set email alerts
|

Acute Interhemispheric Subdural Hematoma: Two Case Reports and Analysis of the Literature

Abstract: Interhemispheric subdural hematoma (ISH) had been considered extremely rare until identification with imaging studies. Its natural history is still quite unknown in terms of potential origin and course. As a consequence of various controversies, there is still no clearly established treatment, particularly in regard to medical or surgical management. The best decision requires tailoring treatment to the individual patient according to his or her clinical condition. Two patients with acute interhemispheric subd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] It accounts for approximately 6% of all traumatic SDH. 1 Head trauma is estimated to comprise 80-90% of the aetiology of ISH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] It accounts for approximately 6% of all traumatic SDH. 1 Head trauma is estimated to comprise 80-90% of the aetiology of ISH.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] We have treated 35 patients with traumatic ISH, and have retrospectively investigated the association between clinicoradiological findings and outcomes in these patients. This study represents the largest series of such patients to be reported and the first analysis of the prognostic factors in patients with traumatic ISH.…”
Section: Introductionmentioning
confidence: 99%
“…The overall mortality rate of ISH is 24-27% 2,14) and is independent of the choice of treatment, indicating that one treatment type (surgical or conservative treatment) is not inherently better 9,14) Those supporting surgical intervention insist that an ISH can have a grave prognosis because of the lack of specific signs and the potential for rapid deterioration of consciousness. These clinicians suggest that prompt surgery via a craniotomy is the only way to deal with this condition safely.…”
Section: Discussionmentioning
confidence: 99%
“…The present state of knowledge gives no definitive indication for surgery in the management of an ISH, with the exception of patients with a large hematoma or rapidly deteriorating level of consciousness despite medical treatment. 9) An ISH is frequently small and often does not require surgical evacuation. In such cases, the natural history of the ISH tends toward spontaneous reabsorption and recovery of the neurological deficits, which can be followed by serial CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation